PENGARUH INTERLAYER PASTA (ZINC+TAPIOKA) PADA SAMBUNGAN FSSW MATERIAL ALUMUNIUM PADUAN - Saputra, Lingga Arti (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Aluminum metal is widely applied in the industrial sector because it has many advantages. FSSW welding is a method that can be used to join aluminum. The microstructural test results show the flow distribution of the zinc interlayer in the welding area. The flow of zinc material looks dominant in the steering zone area. The hardness test results for the connection with zinc interlayer had the highest value of 147HV. Highest shear tensile testing on joints using zinc interlayer. The use of zinc interlayer has been proven to significantly improve connection capabilities.